Exploring Fintech, financial literacy, and stock market participants nexus in Dar es Salaam Stock Exchange, Tanzania - Nathanael, Abraham Charles; Ngollo, Magwana Ibrahim (Asian Management and Business Review, 2025)
This study investigates the relationship between the adoption of financial technology (Fintech), financial literacy, and participation in the stock market in Tanzania, employing a thorough analysis of primary data collected through an online self-reported survey. By implementing purposive sampling techniques, this research executed a series of diagnostic evaluations, encompassing tests for multicollinearity, normality, and heteroskedasticity, to substantiate the integrity of the regression model utilized. The results indicate that the utilization of fintech substantially enhances involvement in stock market activities, thereby corroborating the hypothesis that fintech acts as a facilitator for individual participation in trading activities. Furthermore, the study emphasizes the essential function of financial literacy, suggesting that elevated levels of financial knowledge are positively correlated with an increase in stock market participation. Notably, the effect of fintech on stock market engagement decreased from a coefficient of β = 0.41 to β = 0.19 upon accounting for financial literacy. However, the association persisted as statistically significant (p = 0.002), thereby demonstrating a condition of partial mediation. These findings highlight the fundamental significance of financial literacy as a crucial determinant in fostering active involvement in financial markets. In conclusion, this research provides insightful contributions to the understanding of the interrelations among fintech, financial literacy, and investment behaviors in Tanzania, presenting implications for the formulation of policies, enhancement of financial education, and improvement of market accessibility.